2004
DOI: 10.1191/0269216304pm911oa
|View full text |Cite
|
Sign up to set email alerts
|

Emotional burden of nurses in palliative sedation therapy

Abstract: A significant number of nurses felt serious emotional burden related to sedation. To relieve nurses' emotional burden, we encourage 1) management efforts to reduce work overload, 2) a team approach to resolving conflicting opinions, especially between physicians and nurses, 3) co-ordination of early patient-family meetings to clarify their preferred end-of-life care, 4) education and training about sedation specifically focused on interpersonal skills, systematic approaches to diagnosing refractory symptoms, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 25 publications
5
90
1
11
Order By: Relevance
“…11,[15][16][17]22,23 Similar to other studies, nurses reported PS as an important therapy to improve the care of dying patients with refractory symptoms. Nurses overwhelmingly agreed PS was salient for the management of refractory physical symptoms; however, differences in opinions emerged on whether PS was appropriate for nonphysical symptoms such as depression and existential suffering.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…11,[15][16][17]22,23 Similar to other studies, nurses reported PS as an important therapy to improve the care of dying patients with refractory symptoms. Nurses overwhelmingly agreed PS was salient for the management of refractory physical symptoms; however, differences in opinions emerged on whether PS was appropriate for nonphysical symptoms such as depression and existential suffering.…”
Section: Discussionsupporting
confidence: 66%
“…22 In a nationwide study of Japanese nurses, the lack of understanding surrounding sedation was one of the most frequently cited reasons for emotional burden by nurses. 17 These findings were echoed in our study as nurses cited the importance of clarifying patient eligibility and how PS differed from other treatments.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Implications pour la pratique infirmière L'initiation d'une sédation continue et profonde peut être une expérience difficile pour l'infirmière (Morita, Miyashita, Kimura, Adachi, & Shima, 2004b). L'infirmière joue un rôle central de porteparole auprès du patient à travers le système de santé (Bruce & Boston, 2012).…”
Section: Anxiétéunclassified